(untitled) - Dominiak, Geraldine F. (Boston, 1988)
The 5th edition of this innovative text continues to focus on how managers use accounting information in decision making, planning, and evaluating performance. Time is spent on the basic building blocks of managerial accounting while emphasizing conceptual topics. This text is ideal for both the undergraduate and graduate level Managerial Accounting course.
Keywords: Managerial accounting,Kế toán quản trị